1994
DOI: 10.2337/diacare.17.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of NIDDM in the Pacific Island Population of Western Samoa Over a 13-Year Period

Abstract: This is the first study using standardized methods to show a dramatic increase in the prevalence of NIDDM in a developing Pacific island population, and it indicates the importance of maintaining and expanding preventive programs for NIDDM and related lifestyle diseases in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 0 publications
3
71
0
1
Order By: Relevance
“…However, a major increase in prevalence is apparent (3.4 vs. 7.2%), and this approximate doubling of the prevalence since 1981 was the same whether Busselton was compared with the whole AusDiab sample, with other rural towns, or with the state of Western Australia. Marked increases in diabetes prevalence over the last three decades have also been reported in a variety of developed and developing populations (6,7,20,21). Despite the relatively modest response rate achieved, the current AusDiab results are in keeping with a recent (1992)(1993)(1994)(1995)(1996) large population-based study from the Australian state of Victoria (22).…”
Section: Secular Trends: 1981 To 1999 -2000supporting
confidence: 56%
See 1 more Smart Citation
“…However, a major increase in prevalence is apparent (3.4 vs. 7.2%), and this approximate doubling of the prevalence since 1981 was the same whether Busselton was compared with the whole AusDiab sample, with other rural towns, or with the state of Western Australia. Marked increases in diabetes prevalence over the last three decades have also been reported in a variety of developed and developing populations (6,7,20,21). Despite the relatively modest response rate achieved, the current AusDiab results are in keeping with a recent (1992)(1993)(1994)(1995)(1996) large population-based study from the Australian state of Victoria (22).…”
Section: Secular Trends: 1981 To 1999 -2000supporting
confidence: 56%
“…Duration of obesity is known to be important in the risk of diabetes (29). Although obesity is recognized as an obvious factor associated with the increasing rates of diabetes (20,21,30), the role of physical inactivity is likely to be important and closely inter-related (31). Although there are no long-term trend data for physical activity patterns in Australia, there is evidence elsewhere that the frequency of physical inactivity has steadily increased in recent decades and shows very close parallels with the rising prevalence of obesity (31).…”
Section: Secular Trends: 1981 To 1999 -2000mentioning
confidence: 99%
“…A marked increase in prevalence of NIDDM was found in rural areas also, especially in men. The increase in BMI seen in men and women in the second survey was a strong contributory factor for the increased prevalence of diabetes, although differences in BMI, WHR, physical activity, family history of diabetes or sex did not fully explain the increase in prevalence of diabetes in the Western Samoan population [24].…”
Section: Discussionmentioning
confidence: 81%
“…A follow-up survey of NIDDM in the modernising Pacific Island population of Western Samoa by Collins et al [24] conducted 13 years after a first survey in 1978, showed that the prevalence of NIDDM in urban Apia increased from 8.1 to 9.5 % in men and 8.2 to 13.4 % in women. A marked increase in prevalence of NIDDM was found in rural areas also, especially in men.…”
Section: Discussionmentioning
confidence: 99%
“…About 90-95% of all North American cases of diabetic patients are with diabetes mellitus type 2 [3]. In many other papers the same figures in other parts of the world are given [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%